(untitled) (Stavební obzor - Civil Engineering Journal, 2018)
In the field of civil engineering a diagnostics acoustic non-destructive testing is widely used and in the past years it was used even in testing of high-temperature degraded concrete structures. These methods can provide specific information about the physical-mechanical state of material; however physical-chemical changes in microstructure are measurable to a limited extent. This article is focused on non-destructive and destructive testing of high-temperature degraded concrete test beams of dimensions 0.1 × 0.1 × 0.4 m fired at 200 − 1200 °C. The Impact-Echo method and ultrasonic velocity pulse method measurements are compared with destructive test results. Testing of measured changes in the p-m properties of reference and fired samples is then supplemented by X-ray diffraction analysis, in order to document mineralogical physical-chemical changes of tested material.